THE EFFECT OF TRIP ATTRACTIONS OF KAHAYAN MARKET ON THE CILIK RIWUT STREET - Helenna Yustine Uda (Lambung Mangkurat University Press, 2015)
The development of a city network requires movement (transportation). Transportation factors play an important role where the higher the level of accessibility of the city is, the higher the number of activity nodes becomes. The movement of people and/or goods from one location to another is not an end but a result of a request. The movement caused by the activity sytem and network system is affected by the existing institutions. This research is an experimental research in the area of transportation management in the Province of Central Kalimantan. The object of this research is Kahayan Market and Cilik Riwut Street. This study used five scenarios to solve the problem of traffic congestion that occurs on Cilik Riwut Street. Results of the study can be seen from the results of the five scenarios, where at peak hours the traffic load occurs on the Cilik Riwut Street. Of the five scenarios used, it can be seen the DS and the resulting LOS vary. The best scenario is the one having DS equal to A and LOS ranging from 0 to 20.